ANALISIS PENGARUH HARGA, KUALITAS PRODUK. DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN SFA STEAK & RESTO DI KLODRAN KARANGANYAR - Christian Hari Nugroho, Sunarso & Setyaningsih Sri Utami (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
This study aims to analyze (1) the effect of price to consumer satisfaction (2) the effect of product quality to customer satisfaction(3) the effect of service quality to customer satisfaction. The object of research itself is on restaurant SFA Steak & Resto in Klodran Karanganyar, This study population are all consumers restaurant SFA Steak & Resto in Klodran Karanganyar using a sample of 70 respondents. The technique of collecting data using questionnaires through testing instrument validity and reliability. Test requirements regression using classic assumption test. The conclusion of the test results by using the t test showed that 1) Price does not significantly influence consumer satisfaction at restaurant SFA Steak & Resto in Klodran Karanganyar, this is evidenced by the t test that generates a probability value (0,187) > 0,05. (2) The quality of products significantly influence consumer satisfaction at restaurant SFA Steak & Resto in Klodran Karanganyar, this is evidenced by the t test generates a probability value (0,004) < 0,05. (3) The quality of service does not significantly influence consumer satisfaction at restaurant SFAB Steak & Resto in Klodran Karanganyar, this is evidenced by the t test generates a probability value (0,129) > 0,05.Keywords: price, product quality, service quality, customer satisfaction